Simulating Central-European forests in the 21st century. Effects of climate change, disturbances and management on stocks, productivity and harvests - Manfred J. Lexer; Christoph Pucher; Christian Hochauer; Mathias Neumann; Herbert Formayer; Kristoffer Hasel (Journal of Environmental Management, 2026)

The relationship between plant diversity and aboveground biomass in managed and unmanaged temperate forests - Ameneh Khanalizadeh; Javad Eshaghi Rad; Ghavamodin Zahedi Amiri; Habib Zare; Peter Schall; Manfred J. Lexer (European Journal of Forest Research, 2023)

Effects of single tree selection cutting on vascular plant species diversity components in temperate forests of Hyrcanian region - Ameneh Khanalizadeh; Javad Eshaghi Rad; Ghavamodin Zahedi Amiri; Habib Zare; Peter Schall; Manfred Josef Lexer (Flora, 2023)

Adapting to climate change: an assessment of local adaptation planning processes in forest-based communities in Nepal - Pratigya Silwal; Lin Roberts; Hamish G. Rennie; Manfred J. Lexer (Climate and Development, 2019)

Mountain forest management in a changing world - Manfred J. Lexer; Harald Bugmann (European Journal of Forest Research, 2017)

Evaluating multifunctionality and adaptive capacity of mountain forest management alternatives under climate change in the Eastern Alps - Florian Irauschek; Werner Rammer; Manfred J. Lexer (European Journal of Forest Research, 2017)

Impacts of business-as-usual management on ecosystem services in European mountain ranges under climate change - Harald Bugmann; Thomas Cordonnier; Heimo Truhetz; Manfred J. Lexer (Regional Environmental Change, 2017)

Ecosystem service provision, management systems and climate change in Valsaín forest, central Spain - Marta Pardos; Susana Pérez; Rafael Calama; Rafael Alonso; Manfred J. Lexer (Regional Environmental Change, 2017)

Can current management maintain forest landscape multifunctionality in the Eastern Alps in Austria under climate change? - Florian Irauschek; Werner Rammer; Manfred J. Lexer (Regional Environmental Change, 2017)

Impact of climate change on vulnerability of forests and ecosystem service supply in Western Rhodopes Mountains - Tzvetan Zlatanov; Che Elkin; Florian Irauschek; Manfred Josef Lexer (Regional Environmental Change, 2017)

Adapting Douglas-fir forestry in Central Europe: evaluation, application, and uncertainty analysis of a genetically based model - Debojyoti Chakraborty; Tongli Wang; Konrad Andre; Monika Konnert; Manfred J. Lexer; Christoph Matulla; Lambert Weißenbacher; Silvio Schueler (European Journal of Forest Research, 2016)

Institutional factors and opportunities for adapting European forest management to climate change - Laura Bouriaud; Mariella Marzano; Manfred Lexer; Liviu Nichiforel; Christopher Reyer; Christian Temperli; Heli Peltola; Ché Elkin; Gabriel Duduman; Philip Taylor; Stephen Bathgate; Jose G. Borges; et al. (Regional Environmental Change, 2015)

Using a novel assessment framework to evaluate protective functions and timber production in Austrian mountain forests under climate change - Michael Maroschek; Werner Rammer; Manfred J. Lexer (Regional Environmental Change, 2015)

Exploratory multi-criteria analysis in sustainability impact assessment of forest-wood chains: the example of a regional case study in Baden–Württemberg - Bernhard Wolfslehner; Franka Brüchert; Janine Fischbach; Werner Rammer; Gero Becker; Marcus Lindner; Manfred J. Lexer (European Journal of Forest Research, 2012)

Unraveling the drivers of intensifying forest disturbance regimes in Europe - RUPERT SEIDL; MART‐JAN SCHELHAAS; MANFRED J. LEXER (Global Change Biology, 2011)
Natural disturbances like wildfire, windthrow and insect outbreaks are critical drivers of composition, structure and functioning of forest ecosystems. They are strongly climate‐sensitive, and are thus likely to be distinctly affected by climatic changes. Observations across Europe show that in recent decades, forest disturbance regimes have intensified markedly, resulting in a strong increase in damage from wind, bark beetles and wildfires. Climate change is frequently hypothesized as the main driving force behind this intensification, but changes in forest structure and composition associated with management activities such as promoting conifers and increasing standing timber volume (i.e. ‘forest change’) also strongly influence susceptibility to disturbances. Here, we show that from 1958 to 2001, forest change contributed in the same order of magnitude as climate change to the increase in disturbance damage in Europe's forests. Climate change was the main driver of the increase in area burnt, while changes in forest extent, structure and composition particularly affected the variation in wind and bark beetle damage. For all three disturbance agents, damage was most severe when conducive weather conditions and increased forest susceptibility coincided. We conclude that a continuing trend towards more disturbance‐prone conditions is likely for large parts of Europe's forests, and can have strong detrimental effects on forest carbon storage and other ecosystem services. Understanding the interacting drivers of natural disturbance regimes is thus a prerequisite for climate change mitigation and adaptation in forest ecosystem management.

Climate change vulnerability of sustainable forest management in the Eastern Alps - Rupert Seidl; Werner Rammer; Manfred J. Lexer (Climatic Change, 2011)

Regeneration dynamics in aging black pine (Pinus nigra Arn.) plantations on the south slopes of the Middle Balkan Range in Bulgaria - Tzvetan Zlatanov; Ivaylo Velichkov; Manfred J. Lexer; Tomislav Dubravac (New Forests, 2010)

Testing generalized allometries in allocation modeling within an individual-based simulation framework - Rupert Seidl; Werner Rammer; Panagiotis Bellos; Eduard Hochbichler; Manfred J. Lexer (Trees, 2010)

Modelling bark beetle disturbances in a large scale forest scenario model to assess climate change impacts and evaluate adaptive management strategies - Rupert Seidl; Mart-Jan Schelhaas; Marcus Lindner; Manfred J. Lexer (Regional Environmental Change, 2009)

Erratum to: Multiple-use forest management in consideration of climate change and the interests of stakeholder groups - Cornelia Fürstenau; Franz W. Badeck; Petra Lasch; Manfred J. Lexer; Marcus Lindner; Peter Mohr; Felicitas Suckow (European Journal of Forest Research, 2007)

Multiple-use forest management in consideration of climate change and the interests of stakeholder groups - Cornelia Fürstenau; Franz W. Badeck; Petra Lasch; Manfred J. Lexer; Marcus Lindner; Peter Mohr; Felicitas Suckow (European Journal of Forest Research, 2007)

Regeneration in Gap Models: Priority Issues for Studying Forest Responses to Climate Change - David T. Price; Niklaus E. Zimmermann; Peter J. van der Meer; Manfred J. Lexer; Paul Leadley; Irma T. M. Jorritsma; Jörg Schaber; Donald F. Clark; Petra Lasch; Steve McNulty; Jianguo Wu; Benjamin Smith (Climatic Change, 2001)

Tree Species Composition in European Pristine Forests: Comparison of Stand Data to Model Predictions - Franz-W. Badeck; Heike Lischke; Harald Bugmann; Thomas Hickler; Karl Hönninger; Petra Lasch; Manfred J. Lexer; Florent Mouillot; Jörg Schaber; Benjamin Smith (Climatic Change, 2001)

Tree Mortality in Gap Models: Application to Climate Change - Robert E. Keane; Mike Austin; Christopher Field; Andreas Huth; Manfred J. Lexer; Debra Peters; Allen Solomon; Peter Wyckoff (Climatic Change, 2001)

Ein multi-attributives Nutzenmodell zur Unterstützung der waldbaulichen Entscheidungsfindung dargestellt am Beispiel sekundärer Fichtenwälder - Manfred J. Lexer (European Journal of Forest Research, 2000)

Schätzung von chemischen Bodenparametern für Waldstandorte am Beispiel der Österreichischen Waldinventur - Manfred J. Lexer; Karl Hönninger; Michael Englisch (European Journal of Forest Research, 1999)